The Mughals and the Sufis: Islam and political imagination in India, 1500-1750 - ʿĀlam, Muẓaffar (State University of New York Press, 2021)
Introduction: A long view of Sufism and political culture in India -- The Mughals, the Sufi Shaikhs, and the formation of the Akbari dispensation -- A Sufi critique of religious law, tasawwuf, and politics in Mughal India -- Shah Madar, Sufi religion, and a view of "true Islam" in a Mughal Chishti Tazkira -- Strategy and imagination in a Mughal Sufi story of creation -- In search of a sacred king : Dara Shukoh and the Yogavasisthas of Mughal India -- Piety, poetry, and the contested loyalties of Mughal princesses, c. 1635-1700 -- The Naqshbandi Shaikhs of Sirhind in Aurangzeb's empire and its aftermath.